Effects of Task-oriented Training by Wearing Weighted Vest on the Self-esteem and Activities of Daily Living for Children with Down’s Syndrome: Single System Design - Kwon, Hae Yeon (Journal of International Academy of Physical Therapy Research, 2017)
The purpose of this study was to examine the effects of task-oriented training on the self-esteem and activities of daily living for children Down syndrome. ABA single case research design was applied to this study. Study subjects were instructed to perform task oriented training by wearing weighted vest 12 times in total at the rate of 2 times a week and for 40 minutes each during the intervention, and self-esteem and activities of daily living were measured 3 times in total at the baseline, intervention line and the 2nd baseline stages. There was statistically significant differences in total Pediatric Evaluation of Disability Inventory and activities of daily living scores in accordance with the baseline, intervention line, the 2nd baseline stages (p<.05). This study suggests that task-oriented training by wearing weighted vest improve the total Pediatric Evaluation of Disability Inventory and activities of daily living scores in children with Down’s syndrome. KCI Citation Count: 0